1965
DOI: 10.1039/jr9650000181
|View full text |Cite
|
Sign up to set email alerts
|

28. Photochemical transformations. Part XVI. A novel synthesis of lactones

Abstract: The photolysis of N-iodoamides has been shown to provide a general route to y-lactones. The mechanism and stereochemical aspects of the reaction have been investigated. A general reagent for the preparation of N-iodoamides has been found in t-butyl hypochlorite-iodine.Lactonisation is most conveniently effected by photolysis of the amide in presence of excess of iodinating agent (t-butyl hypochlorite or lead tetra-acetate with iodine).THE synthesis of saturated lactones from saturated acids by oxidative proced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
1

Year Published

1970
1970
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(48 citation statements)
references
References 0 publications
2
45
1
Order By: Relevance
“…Finally, the facile cyclization of bromide 6 to the hydrobromide of iminolactone 7 and other allied cases (13,22,28) requires a comment. Mechanistically, intramolecular nucleophilic substitutions are comn~only recognized to require a 'The corresponding N-chloro derivatives appear to undergo 1,5-chlorine-hydrogen exchangc reaction; the yields are, however, low (13).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the facile cyclization of bromide 6 to the hydrobromide of iminolactone 7 and other allied cases (13,22,28) requires a comment. Mechanistically, intramolecular nucleophilic substitutions are comn~only recognized to require a 'The corresponding N-chloro derivatives appear to undergo 1,5-chlorine-hydrogen exchangc reaction; the yields are, however, low (13).…”
Section: Methodsmentioning
confidence: 99%
“…This has led us to speculate that a II amido radical may react as an N-centered radical (1) as well as an 0-centered radical (3), whereas a B radical will react predominantly as an N-centered species (2 and 4). In view of the well recognized fact that intramolecular hydrogen abstraction generally occurs at the fifth position from the radical center (20)(21)(22), an amido radical may functionalize the alkyl side chain at the 8-or &position depending on the 0-or N-radical character. It is also desirable to establish the preference of hydrogen abstraction from the acyl and the alkyl side chains in anlido radicals since this information may shed light on the electronic configuration of the ground state of arnido radicals.…”
Section: T C Joseph Josiah N S Tam Masayuki Kitadani Et Yuan Lmentioning
confidence: 99%
“…38 For example, Barton used this species to prepare N-iodoamides 39 and to decarboxylate carboxylic acids. 40 Other authors have used it in the preparation of esters from carboxylic acids and alkyl iodides, 41 and in the iodination of aromatics with strong electron donor substituents.…”
Section: Resultsmentioning
confidence: 99%
“…A microanalytical determination of bromine indicated that about 2% of 4-bromopentanoamide could have been formed. Thus lZN-d-Halocarboxamides are known to photochemically rearrange to the 4-halo isomers through a free-radical chain reaction involving an intramolecular hydrogenatom transfer to the amido radical (3,14). For example, N-bromopentanoamide was reported to yield 37% of 4-bromopentanoamide (3).…”
Section: Addition Of Nchloroamides (1 X = Cl) To Cyclohexene (Schemementioning
confidence: 99%